Hate speech in American political discourse: functional-linguistic analysis - Y. Y. Khlopotunov (Дискурс профессиональной коммуникации, 2020)
The aim of this paper is to analyze how the concept of hatred is represented in American political discourse. The problem of intensified hate speech requires thorough linguistic investigation as political discourse is becoming more openly conflictual. The empirical material of this study comprises public speeches by American politicians, politically themed analytical articles in the press, posts and statements of politicians in social networks. The main method is that of functional-linguistic analysis of discourse. The author analyzes confrontational communicative tactics, e.g. discrediting, scorn, insult, accusation, mockery, etc. The objects (or victims) of such rhetoric are political opponents of the subject of speech, who may have different points of view, religious beliefs, cultural backgrounds and social status. Hate speech, which is an extreme form of how the concept of hatred can be verbalized, may be directed against confessional and ethnical groups. The paper puts special focus on communicative goals and intentions of the discourse participants who resort to hate speech. Usually it is the desire of the subject of speech to publicly demonstrate disrespect, mock, belittle the authority of opponents and favorably represent oneself in the eyes of the audience. The rhetoric of hatred comprises such typical means as negative and offensive epithets and metaphors; hyperbolic, comparative, rhetorical and lexical constructions with the pragmatical meaning of irony. In situations, when the subjects of speech emphasize the difference between them and their opponents (national, religious, social etc.), the functional fields of the concept of hatred and the “in-group/out-group” concept may overlap. In these cases, the communicative goal of the speaker is to alienate political opponents and emphasize their dissidence in a negative way.